Review on ubiquitous education system with multi-agent synchronization on mobile learning application environment - Mwinyi, Amir Kombo; Syed Mohamed, Syed Abdul Rahman Al Haddad; Abdullah, Rusli; Hashim, Shaiful Jahari (2012)
The motivation of this study is based on the use of web based learning system from different institutions to embrace the concept of e-learning and m-learning. Due to the mobility nature of these devices and frequency changing of information in the LMS make the process of updating and adding contents together with managing users become very difficult problem. Sync agent is a improved algorithm which solve the problem faced rsync which is a famous open source software tool which is connected to this problem of updating file between two computers or mobile devices. The sync agent (Multi-agent system) proposed algorithm is based on the use of mobile agents which runs from the host (sender) computer and then migrates to the receiving (receiver) mobile computer to continue the process of updating learning contents before coming back to the sender for completing the process. Sync agent which is Multi-agent system is a promising technique which, we believe that, this approach has a potential of increasing the performance of the network and easy learning process by speed up the update process of the mobile learning contents.